1806 Va. Acts 51, ch. 94 - (:unkn) unknown (General Publisher, 1806)
Required every “free negro or mulatto” to first obtain a license before carrying or keeping “any fire-lock of any kind, any military weapon, or any powder or lead.”
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES